Invitations to interview on the role of the library in the undergraduate academic life - Rivera-Aguilera, Alma Beatriz; Carrillo, Salvador; Cruz, Alfredo; Herrera, María Concepción; Salazar-Robles, Sergio; Solano, Gabriela; Horcasitas, Andrea (Qualitative and Quantitative Methods in Libraries, 2019)
This article presents the selection of participants in a study related to the role of the library in University life at two Jesuit universities in Latin America. One of the main objectives of this research is to listen to the voices of students from different origins at the two institutions. Our research team proposed diversity markers that represent different characteristics of undergraduates in our communities based on our experience as professors, the knowledge of our community and the existence of institutional offices that support special groups of students. We used a list of markers of diversity as a base to design a survey that facilitated the selection of participants. Posters invited students to participate; these posters included a QR code to link to the survey. Social networks were used to upload the poster in digital format to a Facebook group with a large number of "friends" from the undergraduate community of one institution. More than 40 students answered the survey, 70% of them were from the University who used social networks. The responses of the survey gave us not only information to select the participants, but also preliminary results of the true diversity of our communities in contrast to our proposal of markers of diversity. These data also provide demographic information beyond what institutions commonly count